A review of fresh properties of 3D printing construction material - Aziz, Muhammad Syahir; Abdullah, Siti Radziah (Recent Trends in Civil Engineering and Built Environment, 2021)
3D printing in construction is a good approach as 3D printing concrete able to harden in short period of time after being produced and the use of formwork is not required. This situation will reduce the construction waste as well increase the efficiently of work. Therefore, the characteristics of 3D material in fresh state is important to fulfilled as printable material. This paper reviews the fresh properties of 3D printing in construction involving the flowability, extrudability and buildability. Any experimental testing related to the flowability, extrudability and buildability of 3D printing will be included as data for the fresh properties. The main objective of this paper is to conduct comprehensive review on fresh properties of 3D construction material for future researches.